Food safety investments in East Africa - Mutua, Florence K.; Grace, Delia; Watts, C. (Purdue University, 2021)
Foodborne diseases are a threat to public health. They also impose an enormous economic burden, affect food and nutrition security, and can hinder market access and disrupt livelihoods. In 2017–2018, the Global Food Safety Partnership (GFSP), a public-private initiative hosted by the World Bank, undertook an intensive analysis of recent food safety investments in sub-Saharan Africa. GFSP built a database of projects and interviewed key informants. We reviewed the food safety investment database, and data related to countries in East Africa was extracted.